Analisis Perbandingan Sistem Ekonomi Kapitalis Dengan Ekonomi Islam - Dewi Rahmi Fauziah; Sarkani Sarkani (STAI La Tansa Mashiro, 2023)
The capitalist economic system is an economic system based on a principle often called the free market and private ownership of economic resources. Meanwhile, Islamic Economics is a science that discusses human behavior in meeting the needs of life based on the rules of Islamic religion. So in designing this research has the aim of comparing a capitalist economic system with Islamic economics in economic, social and ethical aspects. The capitalist economic system is based on the principle of private ownership and competition to achieve economic efficiency in the free market principle, while the Islamic economy involves the principles of justice, sustainability, and equitable distribution of wealth. The research method uses a qualitative approach through extensive, comprehensive literature research, document analysis, and previous journals related to the topic. The data were analyzed to identify the differences, strengths, and weaknesses of each economic system and the associated social and ethical implications. The results of this study show that the capitalist economic system has advantages in promoting economic growth, innovation, and individual financial freedom. However, it also causes significant economic inequality, social inequality, and environmental impacts. The Islamic economic system emphasizes social justice, balance, and participation in productive economic activities. This study provides a better understanding of the differences, strengths, weaknesses, of the capitalist and Islamic economic systems. The study also provides a more comprehensive picture of the social and ethical implications of the two systems. The results of this research study are expected to form the basis for a more inclusive and sustainable future economic policy that combines the strengths of both systems and minimizes the weaknesses. Keywords: Islamic Economy; Capitalist Economy; Qualitative; Comprehensive; Comparison;